Evaluation of measurement uncertainty resulting from the determination of artesunate powder for injection content by a chromatographic technique (HPLC) at the National Quality Control Laboratory of the Democratic Republic of the Congo - NTAMBWE NGOYI, Michel; Lifayifia BISUTA, Béni; Mbinze Kindenge, Jérémie; Marini Djang’ieng’a, Roland (Orapuh Journal, 2025)
Introduction To address the lack of data since the laboratory became operational in 1982, a collaboration was established with the National Quality Control Laboratory (NQCL) of the Democratic Republic of the Congo to evaluate the expanded measurement uncertainty associated with the assay of artesunate powder for injection prior to the routine application of the International Pharmacopoeia, 12th edition (2025) monograph. Purpose To evaluate the expanded uncertainty in accordance with normative requirements during the assay of artesunate powder for injection in order to verify the reliability of the quality control method intended for routine use. Methods The assay was performed according to International Pharmacopoeia, 12th edition (2025), Option A. Analysis was conducted by HPLC using a stainless-steel column (10 cm × 4.6 mm, 3 μm). The mobile phase consisted of 44 mL of acetonitrile R and 56 mL of phosphate buffer adjusted to pH 3.0. A quantity of the mixed contents containing approximately 40 mg of artesunate was accurately weighed. Peak response areas obtained from the chromatograms were measured, and the artesunate content was calculated (specification: 90.0–110.0%). The methodology was based on the Guide to the Expression of Uncertainty in Measurement (GUM), using a bottom-up approach grounded in intra-laboratory data. The measurement process was modelled through a 5M cause-and-effect analysis using an Ishikawa diagram, and uncertainty estimation was carried out using the law of propagation of uncertainty for Type A and Type B components. The parameters shown to have a significant impact on the uncertainty budget were: active pharmaceutical ingredient (API) weighing, HPLC IQ/OQ, volumetric measurements (volumetric flasks), and HPLC response (peak response areas). Results The artesunate content obtained during method verification was 100.3%, with an expanded uncertainty of 0.34%. Taking the calculated expanded uncertainty into account, the reported result was 100.3 ± 0.34%. Conclusion The expanded uncertainty was ±0.34%, and the overall result fell within the acceptable specification range. It can therefore be concluded that the International Pharmacopoeia, 12th edition (2025) method is reliable, as the result is close to the nominal value.